Identification of New Repetitive Element in Leptospira interrogans Serovar Copenhageni and Its Application to PCR-Based Differentiation of Leptospira Serogroups - Michèle A. Barocchi; Albert I. Ko; Suzana Ramos Ferrer; Marcos Tucunduva de Faria; Mitermayer Galvão dos Reis; Lee W. Riley (2001)
A new repetitive DNA element was identified in an isolate of Leptospira interrogans serovar copenhageni from a patient in Salvador, Brazil. A Sau3A genomic library from this strain was constructed and screened for repetitive DNA elements. An insert of 438 bp (Rep1) from one library clone hybridized to multiple chromosomal DNA fragments resolved electrophoretically after digestion with BamHI, HindIII, and MfeI. A single oligonucleotide primer, designated iRepl, was designed to generate multiple PCR amplicons of various electrophoretic mobilities in a PCR typing method. The method distinguished strains belonging to the eight pathogenic and three saprophytic species of the genus Leptospira. Clinical isolates obtained during urban epidemics between 1996 and 1998 in Salvador, Brazil, were analyzed by this PCR method. Although the iRep1 primer was unable to discriminate strains among L. interrogans serovar copenhageni isolates, it was able to differentiate strains belonging to different species and serogroups of Leptospira identified in Salvador. This PCR-based method may provide a faster and less expensive alternative to serologic tests used in reference laboratories.